Toward an Instrumental Right to Democracy. (21st May 2018) - Alfadhel, Khalifa A.
Abstract : The downfall of the Soviet Bloc in the early 1990s led to an atmosphere of exaggerated victory, notably captured in Francis Fukuyama's famous book, The End of History, which celebrated the ideological triumph of democracy as a unanimously agreed-upon ideal form of government. The international law literature was not immune from the sense of democratic rejoicing. Of special note in this regard was the notion of an entitlement to democracy, introduced by the lateThomas Franck . Drawing on ideas of self-determination in international law, which themselves date back to the American Declaration of Independence, Franck postulated an "emerging right to democratic governance." He stipulated that "[s]elf-determination postulates the right of a people organised in an established territory to determine its collective political destiny in a democratic fashion and is therefore at the core of the democratic entitlement." This essay considers Franck's claims, and argues that his view of democracy was too thin; instead, the essay argues for an instrumental conception of democracy that ties it to other rights and entitlements.